Pelatihan Strategi Bisnis UMKM Go Digital Dalam Meningkatkan Daya Saing di Era Digital - Safri, Hayanuddin; Murniyanti, Sri; Firmansyah, Denny; Diah, Muhammad; Sutoyo, Sutoyo; Nurhayati, Agustina; Santika, Cut (Jurnal PKM Manajemen Bisnis, 2025)
The rise of Micro, Small, and Medium Enterprises (MSMEs) in society requires them to keep up with the times. Home-based businesses, or what are commonly called home-based MSMEs, are also now competing on a large scale with their business strategies. As technology continues to develop, so do the strategies for business development, which increases competition. Therefore, in this digital era, where Android is used as a strategy for business growth, MSMEs must compete to expand their businesses, especially by utilizing popular apps like Gojek and Grab. MSMEs that use Gojek and Grab as partners often offer free shipping vouchers and price reductions as part of their strategy to increase sales. However, MSMEs going digital still face challenges in coping with the rapidly evolving digital era. MSMEs that still rely on traditional marketing methods need to work harder to develop business strategies that are now accessible to everyone. A good business strategy is one that creates a competitive advantage. The right business strategy will also ensure the longevity of the company, as desired by the business owner. The purpose of this community service is to improve understanding and enhancement of effective business strategies, especially in the era of digitalization. Many MSMEs close their businesses due to failing in marketing competition, resulting in low profits or, in some cases, no profit at all. This research was conducted to prevent such situations by providing training on business strategies and how these strategies can be used to enhance competitiveness in the digital era. The method used in the training is offline or face-to-face with mentoring, through analysis and problem-solving. The materials provided focus on business strategies to improve competitiveness in the digital era, delivered through lectures, training sessions, Q&A, and demonstrations.